2010
DOI: 10.1186/1471-2458-10-428
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial work load and stress in the geriatric care

Abstract: BackgroundDue to the decrease in informal care by family members and the demographic development, the importance of professional geriatric care will rise considerably. Aim of this study was to investigate the psychosocial workplace situation for employees in this profession.MethodsThe German version of the COPSOQ (Copenhagen Psychosocial Questionnaire) was used for the assessment of psychosocial factors at work. The instrument includes 22 scales and 3 single items concerning demands, control, stress, support, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
52
2
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 13 publications
4
52
2
2
Order By: Relevance
“…time pressure) (Hasson and Arnetz 2007;Kromark et al 2009;Tummers et al 2013). Moreover, nurses in nursing homes have more social interrelations at work (Nübling et al 2010), yielding more social support (Kromark et al 2009) but also more social conflicts (Simon et al 2005;Tummers et al 2013; but see Nübling et al 2010). Notably, the abovementioned factors have all been confirmed to be antecedents of nurses' turnover attitudes and behaviour (Flinkman et al 2010;Hayes et al 2012;Nei et al 2015).…”
Section: Geriatric Care Setting and Nurse Turnovermentioning
confidence: 96%
See 3 more Smart Citations
“…time pressure) (Hasson and Arnetz 2007;Kromark et al 2009;Tummers et al 2013). Moreover, nurses in nursing homes have more social interrelations at work (Nübling et al 2010), yielding more social support (Kromark et al 2009) but also more social conflicts (Simon et al 2005;Tummers et al 2013; but see Nübling et al 2010). Notably, the abovementioned factors have all been confirmed to be antecedents of nurses' turnover attitudes and behaviour (Flinkman et al 2010;Hayes et al 2012;Nei et al 2015).…”
Section: Geriatric Care Setting and Nurse Turnovermentioning
confidence: 96%
“…Notably, the abovementioned factors have all been confirmed to be antecedents of nurses' turnover attitudes and behaviour (Flinkman et al 2010;Hayes et al 2012;Nei et al 2015). So far, large studies have failed to show a direct relationship between geriatric care setting and leaving intentions (Hasselhorn et al 2003;Nübling et al 2010;Tummers et al 2013). A plausible explanation for this might be mediator effects and buffering factors.…”
Section: Geriatric Care Setting and Nurse Turnovermentioning
confidence: 99%
See 2 more Smart Citations
“…However, for those working part-time hours, there was low stress [11]. Similarly in US, a study of female nursing home assistants showed that the odds of adverse mental health increased with increased hours of work [42].…”
Section: Introductionmentioning
confidence: 99%